2021
DOI: 10.1177/0271678x211023660
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based identification of acute ischemic core and deficit from non-contrast CT and CTA

Abstract: The accurate identification of irreversible infarction and salvageable tissue is important in planning the treatments for acute ischemic stroke (AIS) patients. Computed tomographic perfusion (CTP) can be used to evaluate the ischemic core and deficit, covering most of the territories of anterior circulation, but many community hospitals and primary stroke centers do not have the capability to perform CTP scan in emergency situation. This study aimed to identify AIS lesions from widely available non-contrast co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Like other studies combing machine learning and disease models, 27,55 it is hoped the findings of this study would be valuable for clinical practice and to improve patient outcomes. A key point making future translational research promising is that the optimal algorithms and predictive models showed good and stable performance in other external datasets.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Like other studies combing machine learning and disease models, 27,55 it is hoped the findings of this study would be valuable for clinical practice and to improve patient outcomes. A key point making future translational research promising is that the optimal algorithms and predictive models showed good and stable performance in other external datasets.…”
Section: Discussionmentioning
confidence: 91%
“…Four subsets were used as training data and the remaining one as the validation set. The cross‐validation process was repeated five times, and each of the five folds was used once as validation data 27,28 . The results were then averaged to produce a single estimation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson correlation coefficients reported range from 0.44 to 0.76. 5,6,9,10,11 The Dice similarity coefficient reported range from 0.32 to 0.45. 6,10 Among the previous reports, the model reported by Qui et al 5 performed the best.…”
Section: Discussionmentioning
confidence: 99%
“…Contextual information's are used to identify Stroke signs [18,19]. Using widely available NCCT and CT angiography (CTA) data, deep learning can be employed to identify lesions [20].…”
Section: Introductionmentioning
confidence: 99%